2020
DOI: 10.1200/jgo.19.00189
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of Oncology Clinical Trials in Africa

Abstract: PURPOSE The burden of cancer in Africa is of significant concern for several reasons, including that incidence of cancer in Africa continues to rise while Africa is also dealing with communicable diseases. To combat cancer in Africa, oncology clinical trials are needed to develop innovative interventions for cancer prevention, screening, diagnosis, treatment, and survivorship. Unfortunately, there is a paucity of clinical trials in Africa and it is difficult for Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…South Africa is almost never in the first wave of countries in which companies seek registration for new medicines. However, South Africa is an active participant in international clinical trials on new treatments that are being developed for some of the top diseases that represent a high burden of disease in the country such as HIV/ AIDS and cancer [19,20]. Even so many of the treatments tested on patients during clinical trials conducted in South Africa do not eventually get registered in the country [21].…”
Section: Introductionmentioning
confidence: 99%
“…South Africa is almost never in the first wave of countries in which companies seek registration for new medicines. However, South Africa is an active participant in international clinical trials on new treatments that are being developed for some of the top diseases that represent a high burden of disease in the country such as HIV/ AIDS and cancer [19,20]. Even so many of the treatments tested on patients during clinical trials conducted in South Africa do not eventually get registered in the country [21].…”
Section: Introductionmentioning
confidence: 99%
“…What are the common cancer types included oncology clinical trials in Africa? These are the questions that Odedina et al 8 answer in this series. A quantitative, Web-based, retrospective review of clinical trials registries was conducted to develop the landscape of oncology clinical trials in Africa.…”
Section: Emerging Issuesmentioning
confidence: 84%
“…Cancer in Africa has been described as a runaway train as it now kills more Africans than malaria. 1 2 There are an estimated 1 million new cases of cancer on the continent every year and this is expected to double by 2030. 3 Cancer in Africa is characterised by high mortality and the disparity between mortality rates in Africa and high-income countries (HIC) is most striking for childhood cancers with mortality rates as high as 80% compared with 20% in HICs like the USA and Canada.…”
mentioning
confidence: 99%
“…A review of cancer clinical trials in Africa found that only 20 of 54 African countries surveyed hosted clinical trials with the majority in four countries: Egypt, South Africa, Algeria and Kenya. 1 Only 109 cancer clinical trials were being conducted in Africa with a population of 1.2 billion people compared with over 6800 in the USA with a population of 328 million. 15 Regrettably, the exclusion of African participants from the majority of clinical trials means that a large proportion of paediatric patients with cancer are not represented in the very research efforts aimed at combating these diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation